2018
DOI: 10.1016/j.stemcr.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Architecture Is Critical for Mediation of Retinoic Acid Responsiveness by Undifferentiated Spermatogonial Subtypes in the Mouse

Abstract: SummarySpermatogenesis requires retinoic acid (RA) induction of the undifferentiated to differentiating transition in transit amplifying (TA) progenitor spermatogonia, whereas continuity of the spermatogenic lineage relies on the RA response being suppressed in spermatogonial stem cells (SSCs). Here, we discovered that, in mouse testes, both spermatogonial populations possess intrinsic RA-response machinery and exhibit hallmarks of the differentiating transition following direct exposure to RA, including loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 33 publications
(77 reference statements)
3
48
1
Order By: Relevance
“…Our study also showed that higher Oct4-GFP was associated with a more differentiated state and that the gradient of Oct4 induction was paralleled by the gradual loss of self-renewal genes and gain of differentiation-promoting genes. Functionally, we showed that Oct4-GFP-high cells displayed stronger RA responsiveness, which shared the functional property of Id4-GFP-dim progenitors as reported previously (Lord et al, 2018).…”
Section: The Role Of Oct4 In the Regulation Of Ssc Differentiationsupporting
confidence: 87%
“…Our study also showed that higher Oct4-GFP was associated with a more differentiated state and that the gradient of Oct4 induction was paralleled by the gradual loss of self-renewal genes and gain of differentiation-promoting genes. Functionally, we showed that Oct4-GFP-high cells displayed stronger RA responsiveness, which shared the functional property of Id4-GFP-dim progenitors as reported previously (Lord et al, 2018).…”
Section: The Role Of Oct4 In the Regulation Of Ssc Differentiationsupporting
confidence: 87%
“…Studies in mice have shown that a diet deficient in the retinoic acid precursor vitamin A resulted in the accumulation of undifferentiated spermatogonia (Van Pelt & de Rooij 1990, Li et al 2011. Interestingly, it was found recently that somatic cells protect SSC from exogenous retinoic acid while allowing further differentiated cells to respond to retinoic acid in mice (Lord et al 2018). In zebrafish, exposure to a diet low in vitamin D and also to an inhibitor of Aldh1a2 resulted in lower sperm count and fecundity after 3 weeks (Pradhan & Olsson 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The clear implication is that SSCs remain undifferentiated because they lack RARG. However, a recent report challenged this concept by reporting that RARG was detectable in ID4-EGFP+ spermatogonia in the developing testis (Lord et al, 2018). As previously shown in the adult and developing testis (Helsel et al, 2017), the spermatogonial population labeled by the Id4-Egfp transgene is a mixture of those with the highest regenerative capacity (ID4-EGFP bright ; thus, enriched for SSCs) as well as progenitor spermatogonia (ID4-EGFP dim ).…”
Section: Spermatogonia Exhibit a Differential Capacity To Respond To mentioning
confidence: 91%
“…We next addressed whether unequal availability of RA to germ cells following subcutaneous injection at a site distant from the testis in vivo underlies the differential ability of spermatogonia to respond to RA. This could be mediated by several factors, including differential RA concentrations throughout the testis or the effect of distinct spermatogonial niche microenvironments, as suggested recently (Lord et al, 2018). We tested the intrinsic, or germ cellautonomous, responsiveness of neonatal germ cells in vitro by culturing freshly isolated testicular single cell suspensions ±RA for 24 h to maximize the uniformity of RA exposure.…”
Section: Spermatogonia Exhibit a Differential Capacity To Respond To mentioning
confidence: 99%